3 Symphonien - Hartmann, Karl Amadeus 1905-1963 (B.O.A. Videofilmkunst, 2005)
The DVD contains programmes of the TV channel BR Alpha concerning three symphonies by Karl Amadeus Hartmann, as well as the complete recording of the musica viva performance at the Residence in Munich on 29 October 2004, 30 September 2005 and 29 Ocotber 2005. In the data section of this DVD you will find further information on Hartmann, the interpreter and the DVD edition, including many useful Internet links. The DVD provides a very personal insight into the work of Karl Amadeus Hartmann.
Keywords: DVD-Video